Do women only talk about "female issues"? Gender and issue discussion on Twitter. Issue 5 (12th September 2016) - Evans, Heather
Abstract : Purpose: Recent research has shown that female US House candidates were more likely to talk about so-called "female issues" on Twitter during the 2012 election (Evans and Clark, 2015). In this paper, the author extends this former work by investigating the Twitter activity of all US House representatives during their 2012 election and seven months later (June and July of 2013). The purpose of this paper is to show that women do talk more about "female issues" than men, but do not only focus on these issues. Design/methodology/approach: This paper content analyzes the tweets sent by female and male representatives in the 113th Congress during their 2012 elections, and seven months later. Findings: Female representatives spend significantly more time devoted to "female issues" on Twitter than male representatives, but their time is not dominated entirely by "female issues." Even though the difference is not statistically significant, women sent more tweets about "male issues" than men both during and after the 2012 election. Women tweet more than men about "women, " but they also care about business issues, as is evidenced by that issue being one of the most discussed on Twitter by female representatives during both the election and seven months later. Originality/value: Unlike other studies on gender and issue discussion, this paper examines a new type of communication: Twitter. Tweets are split by issue type (female/male) and the author sees that while women do discuss "female issues" more than men, they do not exclude "male issues." This paper also shows that women focus on "female issues" both during elections and after.